2020
DOI: 10.1016/j.jbior.2019.100658
|View full text |Cite
|
Sign up to set email alerts
|

Three dimensional in vitro models of cancer: Bioprinting multilineage glioblastoma models

Abstract: Three dimensional (3D) bioprinting of multiple cell types within optimised extracellular matrices has the potential to more closely model the 3D environment of human physiology and disease than current alternatives. In this study, we used a multi-nozzle extrusion bioprinter to establish models of glioblastoma made up of cancer and stromal cells printed within matrices comprised of alginate modified with RGDS cell adhesion peptides, hyaluronic acid and collagen-1. Methods were developed using U87MG glioblastoma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
72
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 73 publications
(75 citation statements)
references
References 67 publications
0
72
0
Order By: Relevance
“…This was replicated by stimulating angiogenesis through cultured GSCs secreted factors present in the cell medium [ 32 , 35 ]. A recent study managed to recapitulate the heterogeneous glioblastoma tumor microenvironment in bioprinted constructs using an array of cancer and stromal cells including MM6 monocyte/macrophages, U87MG glioblastoma cells, glioblastoma stem cells, microglia and glioma associated stromal cells (GASCs) providing a more realistic chemotherapeutic response [151] ( Fig. 4 -C).…”
Section: Cancer-specific Bioprinted Models For Precision Chemotherapymentioning
confidence: 99%
“…This was replicated by stimulating angiogenesis through cultured GSCs secreted factors present in the cell medium [ 32 , 35 ]. A recent study managed to recapitulate the heterogeneous glioblastoma tumor microenvironment in bioprinted constructs using an array of cancer and stromal cells including MM6 monocyte/macrophages, U87MG glioblastoma cells, glioblastoma stem cells, microglia and glioma associated stromal cells (GASCs) providing a more realistic chemotherapeutic response [151] ( Fig. 4 -C).…”
Section: Cancer-specific Bioprinted Models For Precision Chemotherapymentioning
confidence: 99%
“…Another multinozzle extrusion‐based bioprinting method was used to produce a 3D model with GBM cell lines or GSCs, patient‐derived GBM‐associated stromal cells (GASCs), and microglia in an alginate‐based hydrogel. [ 188 ] The alginate was functionalized with RGDs, and in some groups with HA and collagen. The 3D multicellular models showed moderately enhanced resistance to TMZ and enhanced resistance to cisplatin, a compound that failed many clinical trials but showed promising results in 2D cultures, indicating potential application of this system for more reliable preclinical drug efficacy evaluations.…”
Section: D Bioprinting For Gbm and Bbbmentioning
confidence: 99%
“…Recently, bioprinted alginate–collagen–hylauronic acid matrix comprising of glioblastoma cancer cells was fabricated to control the spatial organization of tumor constructs applied for preclinical drug sensitivity and to study the tumor microenvironment (Hermida et al, 2020). The study shows that the 3D bioprinting of cells has negligible effect on cell viability, and more resistance to anticancer drugs (resembling in vivo condition) than 2D culture.…”
Section: Application Of 3d Culture Techniquesmentioning
confidence: 99%